Gantry Crane Structure Seismic Control by the use of Fuzzy PID Controller - Azeloglu, C. Oktay; Sagirli, Ahmet; Yazici, Hakan; Guclu, Rahmi (GAZI UNIV, 2013)
This paper represents the design of fuzzy PID type controller (FPIDC) to improve seismic control performance of a gantry crane structure against earthquakes. Vibration control using intelligent controllers, such as fuzzy logic has attracted the attention of structural control engineers during the last few years, because fuzzy logic can handle, uncertainties and heuristic knowledge and even non-linearities effectively and easily. The simulated system has a six degrees-of-freedom and modeled system was simulated against the ground motion of the El Centro earthquake. Finally, the time history of the crane bridge and portal legs displacements, accelerations, control forces and frequency responses of the both uncontrolled and controlled cases are presented. Simulation results exhibit that superior vibration suppression is achieved by the use of designed fuzzy PID type controller.
Keywords: Fuzzy PID type controller; Earthquake-induced vibration; Vibration control; Gantry crane structure; Science & Technology - Other Topics